Creativity and Care in times of crisis: an analysis of the challenges of the COVID-19 virus experienced by social work students in practice placement. Issue 8 (17th November 2022) - Hatton, Kieron; Galley, David; Veale, Francisca Christina; Tucker, Gavin; Bright, Colin
ABSTRACT: COVID-19 has had a significant impact on the way social work responds to a wide range of social issues facing PWLE (People with Learned Experience). This paper evaluates a small-scale research project conducted by academics teaching on a United Kingdom (UK) social work degree programme. It explores the experience of students undertaking social work placements and how their practice was impacted upon by the lockdown. The focus concerns the challenges students faced when they were unable to continue their real-time practice placements and instead were asked to undertake virtual learning experiences through the use of Action Learning Sets (ALS) and Blogs. The responses indicate that the students found the use of Action Learning Sets improved their experience during a difficult period. Important lessons can be learned which can contribute to enhancing the educational experience on social work programmes in the UK. These included the recognition of the student voice in delivery, the impact of caring responsibilities, and the need, in future interventions, to directly involve People With Lived Experience in the development and delivery of such initiatives.